The interrelationship and the associated tension between Shari'ah and civil family law in Malaysia: harmonisation as a solution - Kamaruddin, Zaleha (IIUM Press, 2011)
As different family laws apply to different communities within the same national legal system, by right, there should be minimal interrelationship. However, on the few occasions that they interset,there is much confusion and tension created as much by adjective law and juridical issues as the conflicting substantive family laws. The just resolution of these inherently complicated matter is aggravated by a third element seeking to be another, and even overriding source of substantive law-international instrument on certain aspect of family life.